ChemInform Abstract: Stimuli‐Responsive Host‐Guest Systems Based on the Recognition of Cryptands by Organic Guests. Issue 34 (26th August 2014) - Zhang, Mingming; Yan, Xuzhou; Huang, Feihe; Niu, Zhenbin; Gibson, Harry W.
Abstract Review: 76 refs.